Relationship between Age, Gender and Peer Group with Reproductive Healthy Behaviour of Teen - Tetti Solehati; Agus Rahmat; Cecep Eli Kosasih; Nur Oktavia Hidayati (Faculty of Nursing Universitas Padjadjaran, 2018)
Adolescent reproductive health (KRR) in Indonesia is still poor. The KRR known as Triad KRR consisted of sexuality, HIV / AIDS, and drugs become a national problem. Teenagers were more comfortable talking about their KRR with their friends than their parents or teachers. The purpose of this research was to know the relation of age, gender, and peer group with behavior of adolescent reproductive health. The research method was cross sectional study design. Data were analyzed using descriptive statistic, Chi-square and binary logistic. Research conducted in 2017 in junior and high school district Bandung. The population of this study was all students of SMP and SMA amounted to 12,000. The samples amounted 668 students. The results of the research showed that there was a significant relationship between gender with behavior (p = 0,006), there was a significant relationship between age and behavior (p = 0,031), and there was a significant relationship between peer group and behavior (p = 0,042). Multivariate analysis found that age had opportunity 0,527 times, peer group had opportunity 0,211 times, and gender 2,208 times on the behavior support of Triad KRR. The results concluded that KRR behavior is influenced by age, sex, and peer group. Based on the results of the study suggested for the provision of education using a method that involves peer group by considering the age and gender in improving knowledge, adequate and sustainable behavior especially about adolescent reproductive health.